The first data on international multicenter clinical study RheoSTAT-CP0698 on the efficacy and safety of Rheosorbilact® infusion in therapy of pneumonia - Y.I. Feshchenko; S. Beridze; Dinh Thi Hoa; V.Y. Molodtsov; M.I. Gumeniuk; N. Gogoreliani; H.I. Sattarov; N. Emukhvari; G. Lupu; Y.M. Mostovoi; L.M. Kuryk; Nguyen Thi Thu Anh (Infusion & Chemotherapy, 2021)
ABSTRACT. Adequate and effective treatment of severe pneumonia is especially relevant in present situation. The most problematic issue is infusion therapy. The current evidence and guidelines recommend balanced crystalloid infusion for patients with severe pneumonia and sepsis. The composition of Rheosorbilact® provides significant benefits in patients with severe infections, including respiratory infections. According to the results of the randomized open blinded end-point RheoSTAT-CP0698 study, administration of Rheosorbilact® to patients with pneumonia (intravenous infusion at a dose of 200-400 ml/day for 3 days) effectively improves the clinical condition, reduces the manifestations of (multi-) organ failure and endogenous intoxication. Small-volume infusion therapy promotes rapid normalization of circulating blood volume, stabilization of hemodynamics, acid-base, electrolyte and gas composition of the blood, significantly improves saturation and reduces tachypnea. The positive effect of therapy on renal function and inflammation has also been established. This therapy had a favorable safety profile (e. g., it did not lead to fluid overload, pulmonary edema, pleural effusion or other serious side effects, and was not associated with a clinically significant increase in endogenous serum lactate level). The RheoSTAT-CP0698 study substantiates the feasibility of using Rheosorbilact® in the complex treatment of pneumonia.